Implementation of Cognitive Learning Theory Through Coaching Techniques to Understand The Character of Students In Elementary School - Tulis, I Nyoman (Jurnal Indonesia Sosial Sains, 2024)
The purpose of writing this research mini-research is to provide information to readers about how teaching techniques can be applied in education to understand student characteristics to maximize learning. The research method used is qualitative method (literature research), information obtained from various sources such as books, related magazines and phenomenology. The results showed that the application of effective training techniques was: (1) The existence of training; (2) active listening; (3) Effective research. With the correct application of technical competence in training, it can be understood the characteristics of student learning styles, such as; visual learning (learning by seeing), auditory learning (learning and listening), and kinesthetic learning (learning by doing). Teachers can create a more flexible learning environment and develop more effective teaching methods and strategies. From the results of the study, it can be concluded that understanding the characteristics of students both in terms of intelligence and different learning styles can contribute to the emergence of a sense of comfort in learning at school. Learning cannot run well if the techniques or concepts used are the same because students have different characteristics. The application of coaching techniques increases the success of achieving learning objectives without putting pressure on students. In this mode, learning occurs naturally within students, so that learning objectives are easily achieved and beneficial for both teachers and students.